Growth Response and Ionic Relation in Two Brassica Species under Water Stress Conditions: Growth and Ionic Parameters of Brassica - Zaman, Badr-uz-; Salim, M.; Asghar, Rehana; Niazi, B.H.; Mahmood, Imdad Ali; Ali, Arshad (Biological Sciences - PJSIR, 2008)
A glasshouse study of Brassica campestris and Brassica juncea showed that the growth and the ionic parameters of both the species were significantly (p < 0.01) affected due to water stress. Shoot length of both the species decreased consistently with decrease in solute potential (ys) in the root medium. Relative growth rate and dry mass was higher in B. juncea than B. campestris, but leaf area was less. Concentrations of K+, Ca2+, P and S generally decreased with gradual increase in water stress. B. campestris was more susceptible to water stress than B. juncea.